Identification of Heparan Sulfate in Dilated Cardiomyopathy by Integrated Bioinformatics Analysis - Song, Wenyu; Lu, Fujian; Ding, Zequan; Huang, Liqi; Hu, Kui; Chen, Jinmiao; Wei, Lai (Frontiers in Cardiovascular Medicine, 2022)
Background: Heparan sulfate (HS), forming heparan sulfate proteoglycans (HSPGs) to perform biological process, is a key regulator in inflammation and immunity. Whether or how it is involved in dilated cardiomyopathy (DCM) remains little known. Objectives: The aim of this study is to explore the role of HS in the DCM. Methods: Two high throughput RNA sequencing and two microarray datasets, including 301 DCM and 201 normal left ventricle specimens, and one single cell RNA sequencing dataset on DCM hearts were downloaded from gene expression omnibus (GEO) database and integrated for a bioinformatic analysis. Differential analysis, pathway enrichment, immunocytes infiltration, subtype identification and single cell RNA sequencing analysis were mainly used in this study. Results: The expression level of most HSPGs is significantly up regulated in the DCM and is closely associated with immunocytes infiltration, cardiac fibrosis, and failure. Syndecan2 (SDC2) is highly associated with collagen Ⅰ and collagen Ⅲ, the main components of fibrosis, in the level of expression and distribution of cardiac fibroblasts in DCM hearts. Heparan sulfate biosynthetic pathway is activated, while the expression of heparanase (HPSE), the only enzyme to hydrolyze HS, is down regulated in the DCM. Based on the expression of HSPGs, DCM patients can be classified into three molecular subtypes, including C1, C2, and C3. Cardiac fibrosis and failure are more severe in the C1 subtype, which could be identified by the expression of syndecan1 (SDC1), and the abundance of T cells. Conclusion: HSPGs are closely associated with immunocytes infiltration, cardiac fibrosis, and failure in the DCM. A novel molecular classification of DCM is established based on HSPGs.